The Evaluation of the Project on the Development of Mechanism for Academic Supports and Network on Implementing the Buddhist Ways to Good Health: A Moral – Thai - Sufficiency Economy - Oriented Way - Polprasert, Pajaree; Sudsukh, Uthai; Natirutthakorn, Somporn; Chankong, Warangkana (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
The objectives of this research were to: 1. assess the context, input, process, product, and outcomes of the project, and 2. investigate the problems encountered and the factors contributing to the project's success using the CIPP Evaluation Model. The first stage of the research involved assessing these four factors and identifying the problems faced by the project. Data were collected through a questionnaire administered to 68 executives from 13 provinces involved in the project. The data were analyzed using percentage, mean, standard deviation, and content analysis. The second stage focused on assessing the factors contributing to the project's success. This involved a national forum for information exchange, attended by 61 participants, and a local forum with 52 successful project participants sharing their experiences. Data were collected through workshops and in-depth interviews and analyzed using content analysis. The assessment revealed that: 1. Overall, the project was rated as highly appropriate. The context and outcomes were rated as the most appropriate, followed by the input and process, which were considered very appropriate. The main challenges to project success included 1) staff being unable to fully commit to the project due to multiple responsibilities, 2) patients or at-risk individuals missing scheduled appointments, and 3) complicated budget procedures. 2. The factors contributing to the project's success were 1) staff, 2) budget, 3) curriculum, and 4) management. As a result of the project, over 60% of patients or those at risk of hypertension and diabetes were able to maintain desirable blood pressure and blood sugar levels.